INFLUENCER AUTHENTICITY AND HOMOPHILY ON TIKTOK: SHAPING PURCHASE INTENTION VIA PARASOCIAL RELATIONS - Aurellia, Clairene; Dewi, Liliana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Influencer characteristics influence consumer purchase intentions and are increasingly relevant to the digital era, especially through the TikTok platform. The main focus of this study is to analyze the influence of influencer characteristics using homophily, informative value, and authentic variables on the purchase intentions of Gen Z TikTok users in Indonesia, especially in Java, with parasocial relationships as a mediating variable. The research method used is a quantitative approach with a purposive sampling technique, involving 210 respondents aged 18-27 years who actively use TikTok. Data collection was carried out through an online questionnaire with a Likert scale of 1-5, and analysis using SmartPLS. The results of the study showed that homophily had a significant effect on purchase intentions through parasocial relationships. Informative and authentic values did not have a significant effect on purchase intentions through parasocial relationships. These findings emphasize the importance of closeness between influencers and their audiences in building a relationship that can drive purchasing decisions. Keywords: Homophily, Informative Value, Authenticity, Parasocial Relationship, Purchase Intention